Stakeholder Analysis in the Context of Healthcare Entity Managers’ Activities in a Crisis Situation: A Case Study - Głód, Grzegorz; Głód, Wojciech; Rychel, Robert (Journal of Public Governance, 2021)
Objectives: The aim of the article is to present the role of the public manager in crisis management based on the analysis of stakeholders of a selected hospital.Research Design & Methods: Based on the adopted research methodology, an analysis of stakeholders in a selected health care unit was performed. The study used a hospital stakeholder analysis methodology in the context of managing an emergency resulting from the coronavirus pandemic.Findings: The need for a flexible approach on the part of the public manager requires a proper identification of the interests of stakeholder groups as well as the establishment of good communication. In a crisis situation, this approach is particularly important.Implications / Recommendations: On this basis, recommendations were formulated with regard to both theoretical and practical aspects of the research problem. The role of hospital stakeholders in managing a crisis situation is indicated.Contribution / Value Added: Managing a crisis situation in the context of the coronavirus pandemic is a significantchallenge for managers of health care units. In the future, the presented research area can be continued, among other retrospective studies.